G415(P) A 'virtual osce' for mrcpch revision: an efficient and free tool pioneered by trainees for exam success. (May 2019) - Mikolajski, P; White, S; Varughese, R
Abstract : Aims: We identified that we all had individual clinical experiences with conditions commonly seen in the examination. Our aim was to find a way to share this knowledge and recreate this experience by establishing an efficient revision method for the MRCPCH clinical examination. Methods: As a group of three we created simulation OSCE stations based on real patients. Our stations were facilitated by multi-media aids in order to simulate authentic patient encounters; images, videos, audio, diagrams and role-play. These were made available at relevant time points e.g. being shown a picture of arachnodactyly when examining the hands of a 'patient' with Marfan Syndrome. Each person had an important role with individual educational value. The 'examiner' created the scenario. It was necessary for them to have thorough knowledge of the examination and findings, in order to guide the candidate through the station, and conduct a realistic viva question session afterwards. The 'patient' needed to demonstrate realistic findings e.g. high-stepping gait. Finally, the 'candidate' was required to perform a succinct examination and elicit signs. We implemented this technique during a series of revision days. We conducted a real-time OSCE in keeping with MRCPCH timings. Each station included a written vignette with preparation time, followed by the OSCE, warning knock and time for questioning. We performed these in cycles of two, in order to gain practice at changing stations swiftly. Feedback was then provided to the 'candidate' from both the 'examiner' and 'patient', with subsequent general discussion, highlighting specific learning points about each case. Results: At maximum efficiency we completed 30 full clinical cases in a weekend. All three of our group passed the MRCPCH clinical examination first time, with each person reporting at least one successful case that was only previously encountered using this virtual technique. We have subsequently run teaching sessions into utilising our technique to prospective examination candidates. Conclusions: We successfully benefited from pooling individual clinical experiences, to multiply our case exposure. It was both free and efficient. We progressed through many more clinical scenarios than possible with real patients alone, with added benefit of repeating examinations several times.